CESSIE'S JURIDICAL ANALYSIS IN SETTING HOME OWNERSHIP NON-PERFORMANCE LOANS AS A BANK GUARANTEE VIEWED FROM LEGAL POLITICAL ASPECT - Yulfasni, Yulfasni; Hamler, Hamler (PENA LAW: International Journal of Law, 2024)
Politics of banking law (banking law) as the activity of choosing and the method to be used to achieve a particular goal and law, or a legal policy to be applied or carried out includes the consistent implementation of existing legal provisions, the process of updating and making law, which leads to a critical attitude towards law with an ius constitutum dimension and creates a law with an ius constituendum dimension, and the importance of affirming the function of institutions and the development of law enforcers. The problems are 1. How is the cessie in resolving bad loans on housing ownership as bank guarantees from a political and legal perspective? 2. What is the legal power of the auction as a result of creditor guarantee cessie seen from the legal political aspect? and provide answers to these problems. The method used is a type of normative legal research (doctrinaire) with data used secondary data, in the form of primary, secondary and tertiary legal materials. With the conclusion that in the settlement of bad credit, one method can be used with cessie, namely the transfer of rights over intangible goods receivables on behalf of third parties, carried out by selling receivables on behalf of an authentic deed or private deed. And in providing legal protection to cessionaris, they can use retro cessie, which is a means for cessionists whose receivables are not paid by cessus to sue the cedent to ask for the money back.